Uncovering the first complete plastome genomics, comparative analyses, and phylogenetic dispositions of endemic medicinal plant Ziziphus hajarensis (Rhamnaceae) - Asaf, Sajjad; Ahmad, Waqar; Al-Harrasi, Ahmed; Khan, Abdul Latif (BMC genomics, 2022)
Ziziphus hajarensis is an endemic plant species well-distributed in the Western Hajar mountains of Oman. Despite its potential medicinal uses, little is known regarding its genomic architecture, phylogenetic position, or evolution. Here we sequenced and analyzed the entire chloroplast (cp) genome of Z. hajarensis to understand its genetic organization, structure, and phylogenomic disposition among Rhamnaceae species. The results revealed the genome of Z. hajarensis cp comprised 162,162 bp and exhibited a typical quadripartite structure, with a large single copy (LSC) region of 895,67 bp, a small single copy (SSC) region of 19,597 bp and an inverted repeat (IR) regions of 26,499 bp. In addition, the cp genome of Z. hajarensis comprises 126 genes, including 82 protein-coding genes, eight rRNA genes, and 36 tRNA genes. Furthermore, the analysis revealed 208 microsatellites, 96.6% of which were mononucleotides. Similarly, a total of 140 repeats were identified, including 11 palindromic, 24 forward, 14 reverse, and 104 tandem repeats. The whole cp genome comparison of Z. hajarensis and nine other species from family Rhamnaceae showed an overall high degree of sequence similarity, with divergence among some intergenic spacers. Comparative phylogenetic analysis based on the complete cp genome, 66 shared genes and matK gene revealed that Z. hajarensis shares a clade with Z. jujuba and that the family Rhamnaceae is the closest family to Barbeyaceae and Elaeagnaceae. All the genome features such as genome size, GC content, genome organization and gene order were highly conserved compared to the other related genomes. The whole cp genome of Z. hajarensis gives fascinating insights and valuable data that may be used to identify related species and reconstruct the phylogeny of the species.